The Implementation of Dual System Education: A Case Study at the School of Craft Industry Jepara - Amat Mukhadis (Universitas Negeri Malang, 2016)
The study aims at exploring the characteristics of implementation of dual system of education (DSE) at School of Craft Industry Jepara and trying to find the constraints faced by the school and the counterpart institutions. The key persons were administrators and instructors of six small and medium scale industries. An in-depth interview, observation and documentation were used to collect data. Domain analysis was employed to analyze the data. Triangulation was intended to obtain validity of the data. The findings indicate that the DSE is implemented as a field work 'plus', the majority of industries involved are of small scale, the school council does not effectively mediate the school and the industries, the DSE does not result in the expected added values yet, and there are many constraints faced by the school and the industries in implementing the program